(untitled) (Sotang, Yearly Peer Reviewed Journal, 2019)
Health and Illness is a text that looks at health and healthcare through the lens of social epidemiology, critical sociology, political economics and human rights. These perspectives and analyses provide dramatic new insights into our understanding of health, illness and healthcare. Sociological emphasize the health and illness of people is depend on social background. Good health is effective health care system in society; health and illness depend on social construction. Marxist approaches emphasize the causal role of economics in the production and distribution of disease, as well as the role that health knowledge plays in supporting the class structure where as Feminist approaches that pregnancy and child birth is a natural process. Functional talks about the empowerment of women in the society.